Use of theoretical waste inventories in planning and monitoring of hazardous waste management systems - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2014)
Hazardous waste (HW) generation information is an absolute necessity for ensuring the proper planning, implementation, and monitoring of any waste management system. Unfortunately, environmental agencies in developing countries face difficulties in gathering data directly from the creators of such wastes. It is possible, however, to construct theoretical HW inventories using the waste generation factors (WGFs). The objective of this study was to develop a complete nationwide HW inventory of Turkey that relies on nation-specific WGFs to support management activities of the Turkish Ministry of Environment and Urbanization (MoEU). Inventory studies relied on WGFs from: (a) the literature and (b) field studies and analysis of waste declarations reflecting country-specific industrial practices. Moreover, new tools were introduced to the monitoring infrastructure of MoEU to obtain a comprehensive waste generation data set. Through field studies and a consideration of country specific conditions, it was possible to more thoroughly elucidate HW generation trends in Turkey, a method that was deemed superior to other alternatives. Declaration and literature based WGFs also proved most helpful in supplementing field observations that could not always be conducted. It was determined that these theoretical inventories could become valuable assets in supporting regulating agencies in developing countries for a more thorough implementation of HW management systems.
Keywords: Hazardous waste; management; waste generation factor; monitoring; disposal; field study